Effect of partial replacement of NaCl with KCl on physical and sensory traits of dry-cured loin - Kos, Ivica (Array, 2021)
The aim of this study was to investigate the effect of partial replacement of NaCl with KCl on the physical and sensory properties of dry-cured loin. The dry-cured loins were prepared after three treatments, where treatment C served as a control without NaCl replacement, while in treatments F1 and F2, 25 and 37.5 % NaCl was replaced by KCl, respectively. A significant difference (P<0.05) was found in the water activity of the dry-cured loins at all stages between treatments C and F2 and at most stages between treatments C and F1. The study revealed a significantly higher (P<0.05) pH after salting in treatment F2 (5.79) compared to control treatment C (5.58), but no significant differences were found between treatments during the rest of production until the end of storage in vacuum. It was found that there were no significant differences in color values between treatments at all stages of production and storage in vacuum. Among the 17 descriptive sensory traits, significant differences were found only for color uniformity, salty taste and aromatic plant aroma intensity. In contrast, likeability sensory traits like texture and taste likeability, maturity impression, aroma richness and overall likeability were significantly better rated in the control treatment. Considering the adverse effects on likeability sensory traits, replacing NaCl with KCl does not seem to be sufficiently justified. Therefore, further studies are needed as taste improvement could also be achieved by mixing substitutes with a more favourable effect on flavor and other technological indicators, still resulting in lower sodium content.